Pengaruh Perbandingan Tepung Ketan (Oriza sativa L. Var glutinosa) dan Tepung Labu Kuning (Curcubita moschata D.) Terhadap Karakteristik Lappet - Khayrany Sinaga, Royulinar Eksanty; Diah Puspawati, Gusti Ayu Kadek; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 1 (2022): Jurnal ITEPA, 2022)
This study aimed to determine the effect of comparison of glutinous rice flour and pumpkin flour on the characteristics of lappet and to get the right ratio of glutinous rice flour and pumpkin flour on the characteristics of the lappet to produce lappet with the best characteristic. The design used in this study was a completely randomized design with a comparison treatment of glutinous rice flour and pumkin flour consisting of 5 levels, namely: L1 (100%: 0%), L2 (95%: 5%), L3 (90%: 10%), L4 (80%: 20%), and L5 (60%: 40%). Each treatment was repeated 3 times to obtain 15 experimental units. The data were analyzed by analysis of variance and if there was a significant effect, the Duncan Multiple Range Test was perfomed. The results showed that ratio of glutinous rice flour and pumpkin had a significant effect (P<0,05) on ash content, protein content, fat content, carbohydrate content, crude fiber content, beta carotene content, color, aroma, texture, taste, and overall acceptability and had no effect on the moisture content. The ratio glutinous rice flour and pumpkin flour of 60%: 40% produced the best characteristics, water content of 25.59%, ash content of 0.77%, protein content of 1.45%, fat content of 21.70%, carbohydrate content of 50.48%, crude fiber content of 10.78%, beta carotene content of 1467.25 mg/100g and characteristics hedonic brown orange colorand liked, aroma liked, texture liked, taste liked, and overall acceptance liked.